Buying Intentions: Attitudes of Indonesian Consumers - Kuncoro, Amin; Kuncoro, Berlin Setya; Goudia, Amel Dawod Kamel (Journal of Economics and Public Health, 2022)
The purpose of this study is to analyze consumer attitudes toward consumer buying interest. The research design used quantitative descriptive research, data analysis used multiple partial regression analysis using primary data obtained directly from respondents in the form of questionnaire answers. The research sample was visitors who made transactions in the muslin fashion industry in the villages of Muryolobo and Gemiring lor, Nalumsari sub-district, Jepara regency, totaling 150 respondents. The results of the study explain that consumer attitudes can increase buying interest. This proves that consumers who transact are consumers who already understand in detail that the goods needed are in accordance with their needs.